Effect of Oscillation Structures on Inertial-Range Intermittence and Topology in Turbulent Field (Communications in Computational Physics, 2018)
Using the incompressible isotropic turbulent fields obtained from direct numericalsimulation and large-eddy simulation, we studied the statistics of oscillationstructures based on local zero-crossings and their relation with inertial-range intermittencyfor transverse velocity and passive scalar. Our results show that for boththe velocity and passive scalar, the local oscillation structures are statistically scale-invariantat high Reynolds number, and the inertial-range intermittency of the overallflow region is determined by the most intermittent structures characterized by onelocal zero-crossing. Local flow patterns conditioned on the oscillation structures arecharacterized by the joint probability density function of the invariants of the filteredvelocity gradient tensor at inertial range. We demonstrate that the most intermittentregions for longitudinal velocity tend to lay at the saddle area, while those for the transversevelocity tend to locate at the vortex-dominated area. The connection between theramp-cliff structures in passive scalar field and the corresponding saddle regions in thevelocity field is also verified by the approach of oscillation structure classification.